Dual Band RFID-Based for Optimizing Arowana Breading - Hassan, Hasnatul Nazuha (International Journal of Psychosocial Rehabilitation, 2020)
Arowana has made the highest contributor to the country’s ornamental fish with export contribution RM24 millions in 2014. Government expected to contribute a minimum of RM600 million to the gross domestic product by end 2020. An intelligent device is imperative for cost effective to monitor and control the production environment in real time manner. The government encourages developing the best Arowana breeding method. Thus, Arowana farm demand in detecting the active male Arowana to ensure Arowana breeding process is efficient. Arowana farm suffered losses of RM360,000 for 1 fish in a month and time wasted because the reader falls off hands and drowned when the workers are trying to detect the Arowana due to the existing handheld is not intelligent enough and short of capability over water detection for implant tags. The main purpose of this research is to design and develop the intelligent portable reader by using embedded RFID technology that capable to detect the active male to be segregated because the active male will incubates eggs in the mouth and rise to the surface at night. Arowana is a carnivorous fish therefore before the eggs hatch, the active male mouth brooders must be segregated from other Arowana. The fry are faced with the threat from other Arowana if not segregate. Thus, an intelligent radio frequency (RF) portable reader meets the active male mouth brooder detection demand from Arowana farm with the capability of detecting implant tag from outside of the water area. The developed prototype shows that the capabilty of detection for the outdoor setting, it was observed that the maximum distance between the two nodes for the power level of P0 was 160 meters.